Exploring Innovation in Islamic Education through Audiovisual Media in Elementary Schools: A Case Study - Moh. Nizar Hasan Al Mursyidi; Sulyman Muhammad-Busayri (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISHt: Exploring Innovation in Islamic Education through Audiovisual Media in Elementary Schools: A Case StudyObjective: This study aims to identify learning innovations that address students' problems in understanding learning materials at Nurul Ulum Elementary School in Surabaya. Method: This study employs a qualitative method, utilizing interviews and observation for data collection, and the Miles and Huberman model for data analysis. Results: Technological developments have facilitated access to audiovisual media in learning, such as YouTube, and increased the effectiveness of student learning. The role of educators in facilitating learning videos enables more effective and efficient use of learning resources. Conclusion: Learning innovations through audiovisual media at SD Nurul Ulum Surabaya have a positive impact on students' understanding of the material. Readily accessible technology, such as digital platforms and interactive applications, enhances learning effectiveness, with educators playing a crucial role in facilitating their use. Contribution: This research contributes to encouraging the adoption of audiovisual media in Islamic Religious Education learning in elementary schools, as well as providing insight for educators on the importance of integrating technology to improve learning effectiveness and efficiency.INDONESIAN: Eksplorasi Inovasi Pembelajaran Pendidikan Agama Islam melalui Media Audiovisual di Sekolah Dasar: Sebuah Studi KasusTujuan: penelitian ini bertujuan untuk mengetahui inovasi pembelajaran guna menjawab permasalahan siswa terkait pemahaman materi pembelajaran di SD Nurul Ulum Surabaya. Metode: Penelitian ini menggunakan metode kualitatif, pengumpulan data menggunakan wawancara dan observasi, analsiis data menggunakan model Miles dan Huberman. Hasil: Perkembangan teknologi mempermudah akses media audiovisual dalam pembelajaran, seperti YouTube, dan meningkatkan efektivitas belajar siswa. Peran pendidik dalam memfasilitasi video pembelajaran memungkinkan pemanfaatan sumber belajar secara lebih efektif dan efisien. Kesimpulan: Inovasi pembelajaran melalui media audiovisual di SD Nurul Ulum Surabaya menunjukkan dampak positif terhadap pemahaman materi siswa. Teknologi yang mudah diakses, seperti platform digital dan aplikasi interaktif, meningkatkan efektivitas belajar, dengan peran pendidik yang penting dalam memfasilitasi penggunaan media ini. Kontribusi: Penelitian ini berkontribusi dalam mendorong adopsi media audiovisual dalam pembelajaran Pendidikan Agama Islam di sekolah dasar, serta memberikan wawasan bagi pendidik tentang pentingnya integrasi teknologi untuk meningkatkan efektivitas dan efisiensi pembelajaran.